Restauración Forestal de Suelos Secos en El Sector de Alpamalag del cantón Pujilí en el Período 2019 – 2020. - Amaguaña Guanochanga, Nathaly Karolina (2020)
The present research was carried out through a scientific bibliographic compilation to carry out a proposal for forest restoration of dry soils at Alpamalag sector from Pujilí canton. The study area is located at an altitude of 2945 meters above sea level with geographic coordinates of 0 ° 59 ’27” south latitude and 78 ° 40 ’18” west longitude, it is located at northeast. The main objective was to carry out a research for forest restoration of dry soils in the sector. The type of research used was socio-environmental participation, where the affected community is actively incorporated, documentary bibliographic research that allowed to collect scientific information written in theoretical foundation and was a support in the investigation results. In addition, geographic information in downloadable file format from National Information System (SNI) was essential for geographic preparation, soil and climate maps. It was evidenced that Alpamalag de Acurios sector presents a taxonomy of soils within Inceptisols orders, being characteristic fine loamy sand textural class with less than 35% stonyness and in a large proportion the order of Entisols, little evolved soils, with intense erosion and degradation, high stony aggregates. The soil texture in Alpamalag de Acurios sector is largely sandy, with minimal sandy loam and loamy segments. The vegetation cover is primarily intended for the intensive broccoli cultivation, with around 800 hectares. The sector is within the Equatorial Mesothermic Dry climate, with temperatures between 12 and 20 ° C, a rainfall of less than 500 mm with cold air, humidity between 50 - 80% and 1500 hours of sunshine per year. Within the proposal it is proposed to carry out a training plan and environmental awareness aimed at inhabitants of the sector with the participation of students and teachers of Environmental Engineering career of Technical University of Cotopaxi indicating the problem and solution. Also, several endemic forest species were identified that will help to restore the soils, the main ones being Trema micrantha, Ficus cuatrecasana, Schinus molle and Caesalipinia spinosa.